Political economy of energy reform : the clean energy-fossil fuel balance in the Gulf States - Luciani, Giacomo, 1948-; Ferroukhi, Rabea (Gerlach Press, 2014)
Climate change requires coordinated global responses. All nations, including major Gulf Arab oil producers, should implement policies to contain greenhouse gas (GHG) emissions. Yet all realistic scenarios point to the continuing global need for fossil fuels. The countries of the Gulf Cooperation Council (GCC) thus face a dilemma between continuing development and use of their fossil fuel endowments and increasing reliance on low carbon sources, such as nuclear, solar or wind. This book explores various facets of the dilemma._x000B_